Analisis Religius Stimuli Dan Profit Sharing Minoritas Ethnis China Non Muslim Menjadi Nasabah Perbankan Syari’ah Di Kota Palembang - Tariza Putri Ramayanti; Lemiyana Lemiyana (An Nisa'a, 2019)
This research was conducted in theethnis china non muslim customers of Islamic Banks in Palembang city. The purposes of this research are to see how big the influence Religius Stimuli and Profit Sharing towards ethnis china customer’s non muslim Islamic banks. The population of this research is all the non muslim customers who financing. This research used 120 respondents and using Purposive Sampling techniques. Problem solving performed using Structural Equation Model analysis techniques or SEM. From the results of research, the writer obtained the conclution that religius stimuly and profit sharing influenced towards ethnis china Non Muslim Customer.